The Factors of Creative Thinking High School Students In West Java - Oktariani, Mutiya; Dahlan, Dadang (International Conference on Elementary Education, 2020)
Creative thinking skills is one of the fundamental components of 21st-century education that needs to be possessed and developed by students. Thus, the students have the ability to find many alternative solutions to solve problems in economics learning. The study aimed to describe the students' creative thinking skill on the role economics actors topics. The method used is descriptive research with data collection techniques through test deployment (Torrance Test of Creative Thinking) in one school in west java. The participants in this study are 3 classes which consist of 96 K-10 students . The instrument of creative thinking test has been validated by the experts. The result shows that the creative thinking of students is in very less aspect of originality which have the minimum scores is 7.39. That is the ability of students to produce new and unique phrases. It is the most difficult aspect to be trained. In conclusion, students' creative thinking skill on the role of economics actors is still very less, hence, the students are still needed to develop creative thinking ability in the role of economics actors topic